Development and Evaluation of Teaching Materials for a Model Experiment of Visibility of the Moon and Venus - KAWAMOTO Kosuke; KURIHARA Jun-ichi; TOSAKI Tomoka; YAMADA Takayuki (Journal of Science Education in Japan, 2023)
The purpose of this study was to develop teaching materials for a model experiment of the visibility of the moon and Venus in order to improve the understanding and teaching of the visibility of the moon and Venus, as well as to clarify their effectiveness from the viewpoints of both learners and instructors. In developing the teaching material, a 3D printer was used to fabricate gears and a peephole, which are part of the teaching material. This teaching material enables students to become aware of orbits, their directions, and the positions of celestial objects by manipulating the gears, to check the view from the Earth’s perspective through the viewing window while rotating the gears, and to continuously observe changes in the view from the Earth’s perspective.Based on the positive responses to a questionnaire and the results of the survey questions, the use of this material is expected to have a certain effect in understanding the relationship between the positions of celestial objects and the visibility of the moon and Venus from a space perspective, and the visibility of celestial objects from an Earth perspective.